2009
DOI: 10.1080/00288330909509993
|View full text |Cite
|
Sign up to set email alerts
|

Feed intake and its relation to foregut capacity in juvenile spiny lobster,Jasus edwardsii

Abstract: Limited food consumption has been identified as a possible reason for the poor growth in spiny lobsters raised on dry formulated diets. Food intake was determined for different sized juveniles (20-80 g) of the spiny lobster, Jasus edwardsii, fed either fresh mussel flesh or a dry formulated diet for 0.5-5.0 h every 48 h. In addition, the foregut capacities of lobsters of various sizes were measured to relate food intake to foregut fullness. Food intake was relatively rapid on both diets (1 h) and reached mean … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 26 publications
0
18
0
Order By: Relevance
“…Simon and Jeffs (2008) studied feeding and gut evacuation rates in J. edwardsii and reported that a slow appetite revival and diffi culties in processing and digestion of formulated diets appear as major issues to be resolved to improve the performance of formulated diets for spiny lobsters. Simon (2009a) studied feed intake and its relation to foregut capacity in juvenile J. edwardsii. The results indicated that J. edwardsii juveniles have a small foregut capacity (2.5 -3% BW) that limits food intake when diets are fed every 48 hours.…”
Section: Jasus E Dwardsiimentioning
confidence: 99%
“…Simon and Jeffs (2008) studied feeding and gut evacuation rates in J. edwardsii and reported that a slow appetite revival and diffi culties in processing and digestion of formulated diets appear as major issues to be resolved to improve the performance of formulated diets for spiny lobsters. Simon (2009a) studied feed intake and its relation to foregut capacity in juvenile J. edwardsii. The results indicated that J. edwardsii juveniles have a small foregut capacity (2.5 -3% BW) that limits food intake when diets are fed every 48 hours.…”
Section: Jasus E Dwardsiimentioning
confidence: 99%
“…A similar apparent intake (1% BW day À1 ) was also recorded for P. cygnus juveniles (2-7 g) fed a dry pellet (Johnston et al 2007), which is much lower than the daily food consumption of other cultured crustacean such as penaeid shrimps (for instance, 5% BW day À1 in Penaeus monodon; Smith et al 2005b). It was demonstrated that J. edwardsii juveniles cannot achieve high levels of feed consumption on formulated feeds due to a small foregut capacity (2-3% of body weight), expansion of the feed post-immersion and post-ingestion, lengthy foregut filling time (1-2 h) and clearance time (10 h), combined with a slow gut throughput time (34-42 h) and appetite revival (>18 h) (Simon & Jeffs 2008;Simon 2009a). These attributes limit the level of food consumption to the equivalent of the capacity of one foregut per day, that is, 1-1.5% BW day À1 for ingested material with dry matter <50%.…”
Section: Food Consumptionmentioning
confidence: 99%
“…Seawater intake during feeding is an issue that deserves further research because it allows the formulated diet components to dissolve but significantly dilutes the digestive enzymes present in the gastric juice (Simon 2009b;Perera et al 2012b), reduces the maximum dry matter intake per meal (Simon 2009a), and probably elevates the pH of the gastric juice (Simon 2009b). Various studies indicate that the mouthparts of juvenile spiny lobsters are suitable for the mastication of solid food particles (Nishida et al 1990;Wolfe & Felgenhauer 1991;Lemmens & Knott 1994), although early instar juveniles do not appear to effectively manipulate and ingest harder, dry feeds (Cox et al 2008).…”
Section: Food Consumptionmentioning
confidence: 99%
See 2 more Smart Citations